Proyecto de factibilidad para la creación de un hostal para hospedaje y alimentación en el cantón Patate provincia de Tungurahua - Arellano Arellano, María Sol (2015)
This research workisCREATIONOF AHOSTELFORACCOMMODATION ANDFOOD IN THEPROVINCE OFCANTONPATATETUNGURAHUA; ofEcuadorsector considereda privilegedgeographic location thatprovides great benefitsfrom thetourism point of viewdue tothe biodiversity ofthesector;itbeing thesedeterminantsfor theencouragement andpromotion ofall kinds ofactivities and someof these activitiesfactorsisthehosting serviceand food ina hostelthat offersthis type of service, so it was expedientimplementation of thisfeasibility studywhichon analysisgaveexcellent results. Firsthighlight theGeneralPurpose; Determine theFeasibilityfor the Creation ofa hostelforFood and Lodgingin CantonPatatetheTungurahuaProvince. The differentmethods and techniques thatwere used asaredetailed: Deductive-Inductive Method, which served to comparethe surrounding realitywith resultsthat materializedthroughthe conclusionsthat emergedat the endof this investigation, this in turnservedfor the actualrequirementofthe serviceof hostels in thePatate Canton; Analyticalmethodpossible to analyzeeach of theinternal elements, external causesand the relationship betweenthem, which facilitated theanalysis of informationanddata, this methodalsoallowed to knowthe advantagesand disadvantagesof carrying outthisproject;Statisticalmethodfacilitated theinterpretationand understanding ofstatistical dataas wellasthe applicationand tabulationof the respectivesurvey, projections, financial indicators(IRR, NPV, PRC), and thusallowed to knowthe facts aboutHostallifetimethereofuseful. In theMarket ResearchTheMarket Studyof thisprojectit was established thatthe potential demandfor the baseyear is19,823tourists,the real demandis16,849tourists, effective demand 4754, and effective demandinvisitsis33,698services. Technical Study, you can specify the size of theproject will havean installed capacity toprovideservices16,425annually, for which planshave the humanresourcecapacityequipment, tools and expectedlabordays8 hours100% capacity Hostel; thenit was confirmed thatthe most suitable forthe location ofHostalplacein this casewill be locatedon CalleCórdova, among FranciscoPachecoandNovember 18(corner) centerPatate Canton, because the placemeetsthe requirements forimplementation,specificallyregardingaccessroads,utilities,portability,security, basic servicesandfactors detailed inthe weightedmatrixmadefor such analysis. Hostel forroom and board"New DawnCo.: In thestudiedOrganizational, business name with whichoperate the newhostel thatwill bedetermined. Ltda."Also 3 types ofcharts areestablished: Structural, Functional andPositionalalsoa Manual offunctionsisproposedfor existingpositions in theInn. In theFinancial Studyfound thatthe initial investmentof the project isUSD.83267.54; of which, 52% of thetotal investmentcorresponding to$43,267.54will be financed withcontributions from the partners. The loanwill keepthe project withthe Development Bankconstituirá48%which corresponds to$ 40,000a 5year periodto 11.5% annual interest for the purposeof financing theadquisiónof: land, machinery, furniture andadjustments. Finallyin FinancialAssessment,it was determinedthat the NPVis376,653.54; IRRisthe142.54%, being higher than themarket rateobtained; inCost BenefitRatiowas determined thatfor every dollar investedwill getUSD.2.00dollarsofprofit orgain; the initialproject investmentwill be recoveredin the span of1 year, 3 months and 10days;equally inSensitivity Analysisshowed thatthe projectcan supportincreased59.07% increase in its costs,anda59.15% decrease in revenuesfor not gettingnegative net flows. Finallythe resultsdiscussed abovethe analysis inthe developmentof thisproject,we can concludegenerally thatthisprojectgetsa good returnwithpositive balances inall stagesof development, so is consideredfeasibleimplementationone hostelforroom and boardin CantonPatate